(untitled) (Revista Apotheke, 2025)
In this article, we investigate the intersection between art, education, and philosophy, highlighting the importance of dreams and the cosmoperception of Brazilian Indigenous peoples in constructing ways of existence that affirm life. Using a/r/tography as a methodology, which integrates art, research, and teaching, we reflect on creative and educational processes as vital practices. Drawing on the contributions of Nietzsche (1994) and Foucault (2004) regarding life as a work of art, alongside the perspectives of Ailton Krenak (2020) and the Yanomami peoples on dreams, we propose education as a space for the creation of meaning and resistance. The analysis of workshops conducted at the Espacio de Arte Contemporáneo, in collaboration with the Casa de los Sueños in Montevideo, reveals how these practices promote both individual and collective transformation.